2018
DOI: 10.1111/cge.13480
|View full text |Cite
|
Sign up to set email alerts
|

Genetics meets DNA methylation in rare diseases

Abstract: Alterations in epigenetic landscapes are hallmarks of many complex human diseases, yet, it is often challenging to assess the underlying mechanisms and causal link with clinical manifestations. In this regard, monogenic diseases that affect actors of the epigenetic machinery are of considerable interest to learn more about the etiology of complex traits. Spectacular breakthroughs in medical genetics are largely the result of advances in genome‐wide approaches to identify genomic and epigenomic alterations in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…This mechanism plays an important role in human development and disease, primarily by regulating gene expression. 1 Because of the modifiable nature of epigenetic influence, research into DNA methylation has heralded a new era in the elusive search for the route by which the external world might “get under the skin.” 2 By its very nature, this question spans multiple disciplines; geneticists, 3 biologists, 4 computational scientists, 5 neuroscientists, 6 social scientists, 7 and philosophers 8 have been drawn to massive new data about the epigenome with an eye toward how it might explain health, disease, and our very nature. The promise of the epigenetics revolution has been sweeping.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism plays an important role in human development and disease, primarily by regulating gene expression. 1 Because of the modifiable nature of epigenetic influence, research into DNA methylation has heralded a new era in the elusive search for the route by which the external world might “get under the skin.” 2 By its very nature, this question spans multiple disciplines; geneticists, 3 biologists, 4 computational scientists, 5 neuroscientists, 6 social scientists, 7 and philosophers 8 have been drawn to massive new data about the epigenome with an eye toward how it might explain health, disease, and our very nature. The promise of the epigenetics revolution has been sweeping.…”
Section: Introductionmentioning
confidence: 99%
“…Correct DNA methylation is required for normal human development [9]. In principle, alterations of normal methylation patterns can arise in absence of DNA sequence changes (primary epimutation) or secondary to genetic variants that can either occur in cis or in trans (secondary epimutation).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, methylated CpGs that correlate with chronological age and with risk of mortality or developing multi-factorial diseases have been demonstrated [12][13][14]. Specific DNA methylation patterns have been more rarely reported for monogenic diseases [7,9]. DNA methylation can be modified at a single locus generally as consequence of a variant occurring in cis, or at multiple loci possibly as consequence of a variant occurring in trans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progress in epigenetic drugs discovery ( Morera et al, 2016 ; Esteller, 2017 ; Velasco and Francastel, 2019 ), the involvement of epigenetic mutations in a wide range of diseases ( Dirks et al, 2016 ; Graca et al, 2016 ; Jones et al, 2016 ; Berdasco and Esteller, 2019 ) and the newly chromatin-based identified disease biomarkers ( Dirks et al, 2016 ) have suggested epi-based approaches as a promising tool for clinical applications. Evidently, potential new therapeutic options require better clinical knowledge.…”
Section: Discussionmentioning
confidence: 99%